Transition metal complexes of Schiff base ligand based on 4, 6‐diacetyl resorcinol. (5th February 2020) - Mahmoud, Walaa H.; Omar, M.M.; Ahmed, Yasmin M.; Mohamed, Gehad G.
Abstract : Novel Schiff base ligand based on the condensation of 4, 6‐diacetyl resorcinol with 2‐amino‐4‐methylthiazole in addition to its metal complexes with Cr (III), Mn (II), Fe (III), Co (II), Ni (II), Cu (II), Zn (II) and Cd (II) ions have been synthesized. The structure, electronic properties, and thermal behaviour of Schiff base and its metal complexes have been studied by elemental analysis, mass, 1 H NMR, IR spectra, thermal analysis, and theoretically by density function theory. The ligand acted as mononegative bidentate (NO) ligand and all complexes showed octahedral geometry except Cu (II) showed tetrahedral geometry as indicated from the spectral and magnetic studies. The Cu (II), Zn (II) and Cd (II) complexes were non electrolytes while the rest of the complexes were electrolytes. The antibacterial plus anticancer activities of the parent Schiff base and its metal complexes were screened. In addition, the molecular docking study was performed to explore the possible ways for binding to Crystal Structure of Human Astrovirus capsid protein (5ibv) receptor. Abstract : New schiff base ligand and its metal complexes were synthesized and characterized using different tools. Antimicrobial and anti breast cancer screening were evaluated in vitro and give promising results. Some theoretical studies were done to clarify the experimental data.